Assessing rice productivity and adaptation strategies for Southeast Asia under climate change through multi-scale crop modeling - Chun, Jong Ahn; Li, Sanai; Wang, Qingguo; Lee, Woo-Seop; Lee, Eun-Jeong; Horstmann, Nina; Park, Hojeong; Veasna, Touch; Vanndy, Lim; Pros, Khok; Vang, Seng (Agricultural systems, 2016)
Rice (Oryza sativa L.) is one of the most important staple food crops in Southeast Asia, a region that is also particularly vulnerable to climate change. We introduced a multi-scale crop modeling approach to assess the impacts of climate change on future rice yields in Southeast Asia. National- and farmer-level adaptation strategies may be developed by combining the advantages from regional- and field-scale crop models. Climate variables collected from the COordinated Regional climate Downscaling EXperiment (CORDEX)-East Asia were used as inputs to run the GLAM-Rice and CERES-Rice crop models. Simulations produced by the GLAM-Rice model identified Cambodia as the country in Southeast Asia where the reduction in rice yields under climate change will be the largest (a decrease of approximately 45% in the 2080s under RCP 8.5, relative to the baseline period 1991–2000) without adequate adaptation. The results of the model simulations considering the CO2 fertilization effect showed that improved irrigation will largely increase rice yields (up to 8.2–42.7%, with the greatest increases in yields in Cambodia and Thailand) in the 2080s under RCP 8.5 compared to a scenario without irrigation. In addition, the grid cell that will benefit the most (12.6 °N and 103.8 °E) was identified through further investigation of the spatial distribution of the effects of irrigation for Cambodia. For this grid cell, the CERES-Rice model was used to develop the best combination of adaptation measures. The results show that while a doubled application rate of nitrogen fertilizer (100kgNha−1) will increase rice yields by 3.9% in the 2080s under the RCP 4.5 scenario for the Sen Pidao cultivar, a decrease in rice yield was projected for the Phka Rumduol cultivar under RCP 4.5. For both cultivars, the results show that additional adaptation strategies besides the 100kgNha−1 fertilizer application rate and planting adjustment should be applied in order to offset all of the negative projected impacts of climate change on rice yields in the 2080s under RCP 8.5. It is concluded that this study can be useful to enhance food security in Southeast Asia by providing informed recommendations for efficacious adaptation strategies. •We propose multi-scale crop modeling for national and field level adaptations.•Largest decrease in rice yields was projected in Cambodia in the study countries.•Pouthisat and Batdambang provinces may benefit the most from irrigation adaptation.•A best combination of adaptation is proposed to reduce the climate change impacts.